2014
DOI: 10.4168/aair.2014.6.5.421
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Household-level Risk Factors for Self-reported Prevalence of Allergic Diseases Among Low-income Households in Seoul, Korea

Abstract: PurposeIndoor risk factors for allergic diseases in low-income households in Korea have been characterized only partially. We evaluated the prevalences of atopic dermatitis, asthma, and allergic rhinitis in Seoul, Korea, to identify key housing and behavioral risk factors of low-income households.MethodsStatistical analysis of the prevalence of these diseases and various risk factors was conducted using data from a 2010 Ministry of Environment household survey. Logistic regression models were generated using d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…Silvia de Magalhaes Simoes and co-authors showed that 143 (36 %) children of 397 children with bronchial asthma had intermittent course; 160 (40 %) -mild persistent course; 51 (12.8 %) -persistent moderate course and 43 (10.8%) -persistent severe course of the disease [17]. In the same way as in our study the prevalence of allergic rhinitis in children living in Korea or in the Southern Mediterranean region was associated with their place of residence and Dermatophagoides pteronyssinus was the dominant in allergen-induced bronchial asthma [18,19]. The incidence of bronchial asthma and hypersensitivity to domestic allergens was recorded at 12 % vs. 3 % and 56 % vs. 38 % in Lima as compared with Tumbes, and the risk factor for allergic rhinitis development was also the sensitization to domestic allergens [20].…”
Section: Resultssupporting
confidence: 79%
“…Silvia de Magalhaes Simoes and co-authors showed that 143 (36 %) children of 397 children with bronchial asthma had intermittent course; 160 (40 %) -mild persistent course; 51 (12.8 %) -persistent moderate course and 43 (10.8%) -persistent severe course of the disease [17]. In the same way as in our study the prevalence of allergic rhinitis in children living in Korea or in the Southern Mediterranean region was associated with their place of residence and Dermatophagoides pteronyssinus was the dominant in allergen-induced bronchial asthma [18,19]. The incidence of bronchial asthma and hypersensitivity to domestic allergens was recorded at 12 % vs. 3 % and 56 % vs. 38 % in Lima as compared with Tumbes, and the risk factor for allergic rhinitis development was also the sensitization to domestic allergens [20].…”
Section: Resultssupporting
confidence: 79%
“…As shown in Table 5, many Kampong houses and apartment units face problems with mold growth (42% and 37% respectively), which is more than reported in Sweden and Finland (4%) [41,42], and China (5%) [43], but close to that reported in Korea: 35% [44]. According to the mold risk measurements, in Kampongs, 80% of the measured houses are categorized within the highest fungal index, D, an alarming sign, as compared to just 17% of the measurements in apartments ( Figure 5).…”
Section: Mold Risk Mites and Smellsmentioning
confidence: 52%
“…The incidence of asthma is increasing worldwide, but there are still limited serologic biomarkers available 28,29 . We showed that CD93 is significantly associated with allergic inflammation using both in vitro and in vivo models, and the predictive power of CD93 for asthma diagnosis was modest.…”
Section: Discussionmentioning
confidence: 99%